Residual Life Prediction of Railway Axle: A Review: Prediksi umur sisa poros roda kereta api : Sebuah Tinjauan (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Despite being designed to operate for over 30 years, railway axles often experience damage during their service life. Damage can occur as a result of environmental influences, impact from foreign objects, or inherent material imperfections. This paper provides an overview of common damages that frequently occur in railway axles and discusses the fatigue crack growth calculation models used to analyze their remaining life, as well as the parameters that influence fatigue failure in railway axles. Then studies related to fatigue life prediction that has been conducted by several researchers are reviewed. The studies showed that it is important to consider several data variabilities when performing the calculation to produce accurate and reliable results. Keyword: Railway axle fatigue, Residual life prediction, Crack propagation